Biogas Generation from Anaerobic Digestion of High-Content Organic Wastewater - Huu Cong, Vo; Canh, Nguyen Duc (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 3DO - 10.25073/2588-1094/vnuees.4968, 2023)
Animal husbandry activities, industrial development, along with human activities have led to a generation of high organic content wastewater. These wastewater pose severe environmental issues when the BOD or COD exceeded the limit of national regulation. The conventional treatments of wastewater requires high cost whereas large proportion of nutrients in the forms of carbon, nitrogen, and phosphorus being wasted. In the view of circular economy, these wastewater can be simutaneosly treated and recovered as  biogas including CH 4 , H 2 , and N 2 . The efficiency of gas recovery is evaluated through the fluctuations in temperature, pH, and nutrients in the treatment tank. The pH in range of 5.5-6.5 shows the most optimal for H 2 production. The maximum threshold of CH 4 gas generation was obtained from pH 7.6-8.3. The efficiency of H 2 S gas collection is much higher than that of CH 4 and H 2 but it is not feasible to use because of its high toxicity and odor. The essential factors to evaluate the efficiency of nutrient treatment and the production of H 2 and CH 4 in treatment of three types of wastewater above are the BOD/COD ratio and the BOD:N:P ratio.